Exploring Child’s First Language Acquisition within a Bilingual Environment - Nurul Anisa (English Education Study Program FKIP Universitas Alwashliyah Medan, 2025)
This study investigates a child’s first language acquisition within a bilingual Indonesian–Sundanese environment, focusing on how environmental bilingualism influences early pragmatic development. In multilingual societies such as Indonesia, children are frequently exposed to both the national language and a regional language from an early age, raising questions about how such exposure shapes first language acquisition. This study employed a descriptive qualitative research design by examining naturalistic speech data from a 3.5-year-old female child acquiring Indonesian as her first language while being continuously exposed to Sundanese in daily interaction. Data were collected through naturalistic observation and audio recordings of the child’s spontaneous utterances in everyday contexts. The findings reveal that Sundanese phatic particles emerge consistently in the child’s Indonesian speech, indicating bilingual influence at the pragmatic level rather than at the structural level of language. These forms are treated as empirical linguistic data that reflect environmental input and interactional experience. The study concludes that bilingual exposure does not interfere with first language development but instead contributes to the enrichment of pragmatic competence, supporting effective social communication in early childhood.